Analysis of panoramic radiograph and CBCT images of glandular odontogenic cyst in oral cavity: Analisis gambaran radiografi panoramik dan CBCT glandular odontogenic cyst pada rongga mulut - Muh. Akmal Amru; Barunawaty Yunus (Makassar Dental Journal, 2023)
Intraoral or extraoral radiographs are very important for a dentist, especially to see abnormalities that are not visible. The 2D and 3D radiographs can be decisive in establishing the diagnosis of all types of cysts including glandular odontogenic cyst (GOC). In determining the treatment of GOC, 2D and 3D radiographic examinations using panoramic radiographs and CBCT are re-quired. This article examines the role of panoramic radiographs and CBCT in analyzing GOC in the oral cavity. In this litera-ture review, information was collected from several sources, the data was compiled using the matrix method and synthesized information from the literature. It was found that CBCT radiography has high accuracy in detecting and visualizing GOC. It was concluded that based on panoramic and CBCT radiographs GOC are most commonly detected in the mandible. It is character-ized by unilocular lesions, although there are also multilocular lesions.